Exploring factors that impact pass rates in a UK pharmacist registration exam, 2011–2024. - Kavanagh, Oisín N; Ashton, Mark; Husband, Andrew K (International Journal of Pharmacy Practice, 2025)
Objectives: The aim of this work was to evaluate the performance of UK MPharm graduates on the General Pharmaceutical Council's (GPhC) registration assessment, between the years 2011–2024, to explore the factors that impact student performance in this examination. Methods: Student performance in the GPhC registration assessment was contextualized with factors like alma mater, Foundation Training placement, NSS, and HESA data. Relationships between these factors and the weighted average passing rates and raw scores were analysed using a range of statistical methods including correlation analysis, ANOM, Tukey–Kramer, and t-tests. Key findings: Year on year, students from top performing Schools of Pharmacy consistently perform well and performance becomes less consistent as average passing rate decreases (R2 = 0.89; Prob > F < 0.0001). To best discriminate between MPharm programmes and placement type, students can be grouped by their raw score. We also find that students are more likely to pass in hospital compared to community placements, independent of institution. These relationships hold true for the best- and worst-performing students. Conclusions: Our analysis highlights substantial differences in performance levels between the highest and lowest-performing schools and placement types. While not always the case, it appears that pharmacy students should seek to obtain a pre-registration placement in the hospital environment to maximise their chances of success in the GPhC exam. Moving forward, we advocate for better quality data which could link each individual (and their demographic characteristics) as they move through university right through to their performance on each question in the registration exam.